Traditional medicine of ancient Kazakhs in the treatment of tuberculosis: folk methods in the context of modernity (Review) - Pozdnyakova, Yelenа (Ethnobotany Research and Applications, 2024)
Background: Tuberculosis remains a pressing global health issue, with millions affected each year despite ongoing efforts to control its spread. Kazakhstan, like many countries with ancient trade routes, encountered the problem of tuberculosis early in its history, leading to the development of unique and historically rooted treatment methods. This study investigates traditional Kazakh methods for treating tuberculosis, focusing on both historical and botanical sources. The purpose is to identify plants and traditional practices that may offer alternative or complementary treatments for tuberculosis. Methods: The study involved a comprehensive literature review of ancient medical texts and modern databases like Google Scholar, Medline, Scopus, and PubMed. The research included botanical descriptions and analysis of plants' chemical compositions and medicinal properties. Results: In the literature, 11 plant species were found that were historically used as anti-tuberculosis remedies. Significant anti-tuberculosis activity was identified in Xanthium strumarium L., Achillea micrantha Willd., Juniperus communis L., and Anabasis aphylla L.. Additionally, plants like Illicium verum Hook.f., Scutellaria orientalis L., and Veronica arvensis L. show promise for developing new antibacterial drugs. Further research is needed for Cuscuta planiflora Ten., Euphorbia rapulum Kar. & Kir., Potentilla sanguisorba Willd. ex Schltdl., and traditional remedies like Gulkand to explore their potential medical applications. Conclusions: The findings highlight the relevance of traditional Kazakh medicine in contemporary contexts, especially in light of rising antibiotic resistance. The study suggests that further research into these plants could lead to innovative treatments for tuberculosis and other infectious diseases. Keywords: Traditional Medicine, Tuberculosis, Kazakh Ethnobotany, Medicinal Plants, Antibiotic Resistance